Keputusan Pembelian Dan Determinan Yang Memengaruhi Ekuitas Merek Madu Kemasan Madurasa - Purnomo, Prastika Adelia; Nurmalina, Rita (Forum Agribisnis, 2024)
Honey is a secondary food product which included in nutraceutical products with health functions for human body. The demand of honey products continues to increase and has made many brands of packaged honey compete. Madurasa has been the top brand in the branded packaged honey category, which indicates that Madurasa has strong brand equity. Therefore, this research aims to find out the purchasing behavior patterns of Madurasa consumers and what determinants can affect brand equity. The study takes place in Jabodetabek from October 2022 to September 2023, utilizing primary data from online questionnaires. The analytical methods used are descriptive analysis, cross tabulation and SEM- PLS. The analysis results show that Madurasa consumers make pre-planned purchases of Madurasa products. Madurasa consumers prefer purchasing products in plastic bottle at Minimarkets. They typically buy one or two products per purchase and consume them two or three times a week. The brand equity dimensions that significantly influence Madurasa’s brand equity are brand awareness, perceived quality, and brand loyalty. Based on these results, Madurasa can expand product distribution, carry out intensive promotions and innovate product types and packaging to increase these dimensions.